Chemogenetic Stimulation and Silencing of the Insula, Amygdala, Nucleus Accumbens, and Their Connections Differentially Modulate Alcohol Drinking in Rats - Haaranen, Mia; Schäfer, Annika; Järvi, Vilja; Hyytiä, Petri (Frontiers in Behavioral Neuroscience, 2020)
The anterior insular cortex is hypothesized to represent interoceptive effects of drug reward in the service of goal-directed behavior. The insula is richly connected, but the insula circuitry in addiction remains poorly characterized. We examined the involvement of the anterior insula, amygdala, nucleus accumbens, as well as the projections of the anterior insula to central amygdala, basolateral amygdala, and nucleus accumbens core in voluntary alcohol drinking. We trained alcohol-preferring AA (Alko Alcohol) rats to drink alcohol during intermittent 2-hour sessions. We then expressed excitatory or inhibitory designer receptors (DREADDs) in the anterior insula, nucleus accumbens, or amygdala by means of adenovirus mediated gene transfer and activated the DREADDs with clozapine-N-oxide (CNO) prior to the drinking sessions. Next, to examine the role of specific insula projections, we expressed FLEX-DREADDs in the efferent insula→nucleus accumbens core, insula→central amygdala, and insula→basolateral amygdala projections by means of a retrograde AAV-Cre vector injected into the insula projection areas. In the anterior insula and amygdala, excitatory Gq-DREADDs significantly attenuated alcohol consumption. In contrast, in the nucleus accumbens the Gq-DREADD stimulation increased alcohol drinking and the inhibitory Gi-DREADDs suppressed it. The Gq-DREADDs expressed in the insula→nucleus accumbens core and insula→central amygdala projections increased alcohol intake, whereas inhibition of these projections had no effect. These data demonstrate that the anterior insula, along with the amygdala and nucleus accumbens, has a key role in controlling alcohol drinking by providing excitatory input to the central amygdala and nucleus accumbens to enhance alcohol reward.